To solve the given systems of equations by substitution, let's put the steps in a logical order:
-
Rewrite one of the equations to express one variable in terms of the other:
\( x - 2y = 11 \) → \( x = 2y + 11 \) -
Substitute this expression into the other equation to eliminate one variable:
Substitute \( x = 2y + 11 \) into the equation \( -7x - 2y = -13 \)
\( -7(2y + 11) - 2y = -13 \) -
Expand and simplify the substituted equation:
\( -14y - 77 - 2y = -13 \) → Combine like terms
\( -16y - 77 = -13 \) -
Isolate the variable:
Add 77 to both sides:
\( -16y = 64 \)
Divide by -16:
\( y = -4 \) -
Substitute the value of \( y \) back into the expression for \( x \):
\( x = 2(-4) + 11 \)
\( x = -8 + 11 \)
\( x = 3 \) -
Identify the solution:
So, the solution is \( (x, y) = (3, -4) \)
The correct order of the steps is:
- \( x - 2y = 11 \) → \( x = 2y + 11 \)
- Substitute: \( -7(2y + 11) - 2y = -13 \)
- Expand: \( -14y - 77 - 2y = -13 \)
- Combine: \( -16y - 77 = -13 \)
- Isolate: \( -16y = 64 \)
- Solve for \( y \): \( y = -4 \)
- Substitute \( y \) back: \( x = 2(-4) + 11 \)
- Find \( x \): \( x = 3 \)
- Solution: \( (3, -4) \)